La influencia de la fibra de bambú en las propiedades mecánicas de un bloque de tierra comprimido - Andrade Moreno, José Antonio (2018)
Abstract:The function of this work concretes significant aspects for the understanding, use and elaboration of the BTC, reinforced with bamboo fiber and Guadua, gathering necessary information to display its applicability in rural areas of the country, mainly serving as a contribution in the province of Loja and specifically in the canton Catamayo from which the materials will be obtained. The study is aimed at obtaining the resources ¨ land and bamboo ¨, present in the area to develop the work, which will proceed to make an analysis of the type of soil that is provided for this application thus observing its feasibility in the elaboration of the element. From Bamboo and Guadua fiber will be obtained to serve as a reinforcement and increase the strength in the mechanical properties of said block. At the end of the present, we mainly discuss the compressive strength of the BTC obtained, presenting favorable results for its application in the construction, in addition to the importance of the optimum humidity percentage for its elaboration and relevant aspects with respect to the Bamboo fiber. - Guadua related to the resistance of the element.